A review of the effect of stability issues and wide-bandgap in the application of perovskite solar cells - Prince Tshepho Mokabane; Valantine Takwa Lukong; Tien-Chien Jen (Materials for Renewable and Sustainable Energy)
Abstract Research into perovskite solar cells (PSC) is making significant progress toward contributing to renewable energy generation. With perovskite solar cells, power conversion efficiency above 25% has been reported, making it a promising technology. The existing module perovskite-based type cells indeed display the best performance of all the types available in the markets, even with the excess temperature conditions as concerns. However, the chances of perovskite-based types providing sustainable energy are low, and more work is still required. This article discusses predictions about workability issues and the existence of a high forbidden zone that came with PSCs. It then reviews the degradation mechanisms and solutions to overcome these stability problems. PSCs have a big commercialization issue, which may concern their stability because their productivity is unstable in real-time operation, especially under long run-time conditions. In addition, the review expands on how PSC materials effectively transport charges and how the various barriers present in PSCs are affected. The article goes into more detail on how perovskite crystal orientation has lately been significant, which modern design is suitable for perovskite solar cells, how different layers in perovskite cells are made, and what kind of materials are laid between electron transport layers (ETLs) and buffer layers. The final part of the article provides insight into the methods for overcoming degradation and enhancing the stability PSCs, which is crucial for commercialization.